Independence as a Moderating Influence of Gender and Religiosity on Audit Judgment - Nanda putri aprilianti; Umi Muawanah; Khohar Adi (Fakultas Ekonomi Universitas Kadiri, 2023)
The purpose of this study was to explain the effect of gender, religiosity as independent variables and auditor independence as moderating variables on audit judgment as the dependent variable. The researchers conducted a research at several Public Accounting Firms (KAP) in East Java. This study uses the associative method to analyze the causal relationship between the variables of gender, religiosity on audit judgment with independence as a moderating variable. The results showed that Gender had no significant effect on the Judgment audit, religiosity had a significant effect on the Judgment audit, the interaction between Independence and Gender on the Judgment audit, showed that Independence weakened the influence of gender on the Judgment audit, and the interaction of Independence and Religiosity on the Judgment audit showed that Independence strengthened the effect of religiosity on the Judgment audit